Jumpstart! music ideas and activities for ages 7-14 - Foster-Peters, Kelly-Jo (Routledge, Taylor & Francis Group, 2020)
"Children develop their musicality best through engaging and participating, and an effective and enriching music curriculum must focus on the development of practical music-making skills. Jumpstart! Music therefore contains a wealth of ideas and activities that will support any teacher as they aid the musical learning of pupils aged 7 to 14, helping students not only to learn in new and exciting ways, but also to enjoy themselves while they are doing it. Inspiring any young learner to listen to, make and create a range of music, the book includes multiple simple-to-use ideas and activities, with every chapter based around fun and engaging topics, such as: Storytelling History Media Modern music Technology The world With group suggestions as well as opportunities for the students to develop their skills independently, the games and ideas featured in this title all focus on the core skills in learning music - listening, singing, playing improvising, composing and SMSC (spiritual, moral, social, cultural) - and are all flexible enough to be adapted to fit each individual situation, whatever the resources to hand. Jumpstart! Music is an essential classroom resource for helping young learners develop their musicality and musicianship and will support any teacher in delivering engaging, inclusive and creative music lessons"--
Description based on online resource; title from digital title page (viewed on June 24, 2020)
Keywords: School music / Instruction and study / Activity programs